2023
DOI: 10.1002/ar.25132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electroacupuncture on glial scar generation in SCI model rats

Abstract: Spinal cord injury (SCI) is a commonly occurring and severe form of central nervous system (CNS) injury. Previous studies have demonstrated that electroacupuncture (EA) therapy promotes recovery from SCI. In this study, we observed changes in the glial scars of rats with SCI to gain insight into how EA therapy positively influences locomotor function. The experimental rats were randomly divided into three groups: the sham group, the SCI group and the SCI + EA group. Rats in the SCI + EA group received a 28‐day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…1.4 | Novel potential mechanisms of acupuncture in treating nervous system diseases Spinal cord injury is the most serious complication of spinal injury, which leads to severe motor and sensory dysfunction. Based on the current situation of side effects and complications of drug therapy, Hu et al (2023) explored the influence of EA on the function of injured spinal nerves, to provide safer and more effective treatment methods. They found that the morphology of injured spinal cord tissue was improved, and glial scar and cavity were reduced by EA at Dazhui (GV14) and Mingmen (GV4) acupoints in spinal cordinjured rats.…”
Section: Investigating the Potential Mechanism Of Tcm-based Therapy I...mentioning
confidence: 99%
“…1.4 | Novel potential mechanisms of acupuncture in treating nervous system diseases Spinal cord injury is the most serious complication of spinal injury, which leads to severe motor and sensory dysfunction. Based on the current situation of side effects and complications of drug therapy, Hu et al (2023) explored the influence of EA on the function of injured spinal nerves, to provide safer and more effective treatment methods. They found that the morphology of injured spinal cord tissue was improved, and glial scar and cavity were reduced by EA at Dazhui (GV14) and Mingmen (GV4) acupoints in spinal cordinjured rats.…”
Section: Investigating the Potential Mechanism Of Tcm-based Therapy I...mentioning
confidence: 99%
“…In addition, Ling Hu suggested that EA could decrease serum LH and FSH levels and also increase serum E2 and hypothalamus in a perimenopausal model of β Endophilin (β-enkorphin, β-EP) content, and increase uterine visceral index and endometrial thickness [13][14][15].…”
Section: Moxibustionmentioning
confidence: 99%